Curcumin encapsulation using dendrimer PAMAM G4 conjugated with polyethylene glycol to improve the properties of gel dossage form - Rahmah Elfiyani; Yudi Srifiana; Faisal Dharojat Al Rasyied (Universitas Ahmad Dahlan, 2018)
Curcumin had a low bioavailability, to improve it than curcumin was encapsulated in the PAMAM dendrimer conjugated PEG. To facilitate topical use, curcumin dendrimer was combined with a carbomer 940 that can produce hydration conditions in the stratum corneum so as to increase the bioavailability of curcumin. This study aimed to obtain the ratio between curcumin with dendrimer of PAMAM G4: PEG in the formation of curcumin dendrimer combined in the base of carbomer 940 to produce the optimal of physical characteristics of dendrimer and physical stability of gel. The study was conducted by conjugating PAMAM G4 with PEG with a ratio of 1:5, and then encapsulated curcumin in dendrimer with a ratio of 1:0.2 (F1); 1:0.02 (F2) and 1:0.002 (F3). Further dendrimers that have encapsulated curcumin were formulated in a gel with a carbopol base 940. The physical characteristics of the gel tested were polydispersity index, zeta potential and particle size, organoleptic, flow properties, and pH at weeks 0, 2, 4 and 6. The results shows that F1 has zeta potential highest and the lowest viscosity of the other formula, while F3 has the lowest potential zeta and highest viscosity of other formulas. In addition, the polydispersity index, particle size, organoleptic, flow properties and pH; there are not a significant difference in each formula, but the particle size, zeta potential, and viscosity of gel can decrease with longer storage time. Conclusion of this study that the ratio between curcumin and dendrimer PAMAM G4:PEG of 1: 0.2 shows the optimal of physical characteristics of dendrimer and physical stability of gel.